(3HOjYjI GdTjN ESeGYjd Hf GdMSjf GdNRQLis - (3ESeGYjd Hf GdMSjf GdNRQLjs ((3YeQ CfSi Hf eMeO OjH GdUbYGf GdHjQhJi s)
(3ChdgG (B:s
(3HQGYJi QGb efgG eWdY GdcdGe MSf EaJJGMi HgG ai YQH Pi Sde s
(3BNQgG (B:s
(3hGQMe MSjfkG hLO Hjf GdHQjI di HMSf NGJeI jG HGQF GdfSe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdHdGZIs